Targeting MALT1 Suppresses the Malignant Progression of Colorectal Cancer via miR-375/miR-365a-3p/NF-κB Axis - Qian, Rui; Niu, Xinli; Wang, Yinghui; Guo, Zhi; Deng, Xuyi; Ding, Zhenhua; Zhou, Meijuan; Deng, Haijun (Frontiers in Cell and Developmental Biology, 2022)
Colorectal cancer (CRC) is a malignant tumor with the second highest morbidity and the third highest mortality in the world, while the therapeutic options of targeted agents remain limited. Here, mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1), known as upstream of NF-κB signaling pathway, was identified to be highly upregulated in CRC tumors and cell lines. Furthermore, downregulation of MALT1 or inhibition of its proteolytic function by MI-2 suppressed cell proliferation and migration of CRC cells. In vivo, suppressing MALT1 expression or its proteasome activity effectively reduced the size of subcutaneous tumor in nude mice. Mechanistically, miR-375 and miR-365a-3p were identified to inhibited NF-κB activation via targeting MALT1. Overall, our results highlight that a novel regulatory axis miRNA-MALT1-NF-κB plays a vital role in the progression of CRC and provide novel and hopeful therapeutic targets for clinical treatment.